The essential Peter S. Beagle. Volume 1, Lila the Werewolf and other stories - Beagle, Peter S. (Tachyon Publications LLC., 2023)
The essential first volume of bestselling author Peter S. Beagle's short stories demonstrates why he is one of America's most influential fantasists. With his celebrated versatility, humor, and grace, Beagle is at home in a dazzling variety of subgenres. Evoking comparison to such iconic authors as Twain, Tolkien, Carroll, L'Engle, and Vonnegut, this career retrospective celebrates Beagle's mastery of the short-story form. An unlikely friendship based on philosophy develops between an aging academic and a mythological beast. A mysterious, beautiful attendee who attends a ball thrown in her honor chooses whether or not to become mortal. A dysfunctional relationship is not improved by the consequences of lycanthropy. One very brave young mouse questions his identity and redefines feline wiles. From heartbreaking to humorous, these carefully curated stories by Peter S. Beagle show the depth and power of his incomparable prose and storytelling. Featuring an original introduction from Jane Yolen (Owl Moon) and gorgeous illustrations from Stephanie Pui-Mun Law (Shadowscapes), this elegant collection is a must-have for any fan of classic fantasy.